Enhanced Growth Rates of the Mediterranean Mussel in a Coastal Lagoon Driven by Groundwater Inflow - Andrisoa, Aladin; Lartaud, Franck; Rodellas, Valentí; Neveu, Ingrid; Stieglitz, Thomas C. (Frontiers in Marine Science, 2019)
Groundwater discharge is today recognized as an important pathway for freshwater, nutrients and other dissolved chemical substances to coastal systems. While its effect on supporting primary production in coastal ecosystems is increasingly recognized, its impact on growth of animals at higher trophic level (primary and secondary consumers) is less well documented. Here we investigate the impact of groundwater discharge on the growth of the Mediterranean mussel (Mytilus galloprovincialis) in a coastal lagoon. Growth rates and condition index (tissue weight / shell weight) of mussels growing at groundwater-exposed sites and at a control site in Salses-Leucate lagoon (France) were measured. The mussels in this lagoon produce circadian (daily rhythm) growth increments in their shell, as opposed to semi-diurnal increments in tidally influenced systems. Mussels from groundwater-influenced sites have higher growth rate and condition index compared to those from a control site. Importantly, growth rates from groundwater-influenced sites are amongst the highest rates reported for the Mediterranean region (41 ± 9 μm d-1). The higher growth rates at groundwater-influenced sites are likely a consequence of both the higher winter temperatures of lagoon water as a result of groundwater discharging with relatively constant temperatures, and the groundwater-driven nutrient supply that increase the food availability to support mussel growth. Overall, this study demonstrates that groundwater discharge to Mediterranean lagoons provides favourable environmental conditions for fast growth of mussels of high commercial-quality.